Copernicus Festival 2016: Beauty - Urbańczyk, Piotr (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2016)
Copernicus Festival, held annually, aims to demonstrate various dimensions of the relationship between science and culture. The third edition of the festival was devoted to the concept of beauty. During the six days of the festival about 7 thousand people took part in lectures, debates, discussions, workshops, concerts and other events.